2012
DOI: 10.1063/1.3686430
|View full text |Cite
|
Sign up to set email alerts
|

Plastic behavior of polycrystalline tantalum in the 5 × 107/s regime

Abstract: Abstract. The goal of this experiment was to investigate the plastic response of Ta to dynamic loading at high strain rates. The samples used were derived from high purity rolled plate, polished down to thicknesses in the range 25-100 μm. Dynamic loading was applied by direct laser ablation of the sample, with pulses up to 10 ns long, at the Jupiter Laser Facility. The elastic-plastic wave structure was measured using two line VISAR systems of different sensitivity, and strain rates were inferred from the rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
1
2
0
1
Order By: Relevance
“…4. Several previously reported results are also shown [9,10,41]. The figure shows that the current yield stress measurements are sensitively -dependent on the rise time in both shock and ramp compression loading such that higher yield stress obtains for a shorter rise time.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…4. Several previously reported results are also shown [9,10,41]. The figure shows that the current yield stress measurements are sensitively -dependent on the rise time in both shock and ramp compression loading such that higher yield stress obtains for a shorter rise time.…”
Section: Resultssupporting
confidence: 59%
“…The rise in the strain-rate-dependent stress is greater at shorter rise times. Higher strain rates than predicted by the constitutive model of Eggert et al [9] as well as by the referenced experimental measurements [10,41] are shown to have been achieved.…”
Section: Resultsmentioning
confidence: 72%
“…Further experimental details on the laser experiments can be found elsewhere. 14,15 Electron backscattered diffraction (EBSD) orientation mapping was used to characterize the texture in the samples and observe instances of twinning. To prepare samples for EBSD examination, the observed surfaces were polished to a 0.5 µm finish to minimize the surface damage.…”
Section: Methodsmentioning
confidence: 99%
“…Shock-loaded Ta has been studied using both gas-gun [29] and laser-driven shocks [30e32]. These experiments show a rich behavior, including high strength [32,33], dislocations [29e31], twinning above a critical pressure around 40 GPa [30,31,34,35], and the presence of uphase [30,31] in some recovered samples shocked above w70 GPa.…”
Section: Introductionmentioning
confidence: 99%